تطبيقات المعيار الذاتي في نظرية التعسف في استعمال الحق وفقاً للقانون المدني الأردني: عرض وتحليل : (Applications of the Subjective Criterion in the Theory of Abuse of Rights under the Jordanian Civil Code: A Presentation and Analysis) - ياسمين محمد خالد منصور (At-Tajdid - Intellectual Refereed Journal, 2026)
This study addresses an important subject, namely the applications of the subjective criterion in the theory of abuse of rights under the Jordanian Civil Code: an analytical and descriptive examination. The research aims to elucidate the concept of the theory of abuse of rights, to examine and analyse the subjective criterion within this theory, and to identify its applications in matters of personal status and under the Jordanian Civil Code. The research problem arises from the need for an in-depth analysis of the subjective criterion in the theory of abuse of rights and its practical application in personal status matters and Jordanian civil law. The study adopts an inductive and applied methodological approach. The findings indicate, inter alia, that the theory of abuse of rights is founded upon a set of legal principles that seek to prevent conduct that contradicts the intent of the Lawgiver in actions that are, in principle, legally permissible, thereby realising the objectives of the Sharīʿah with regard to rights and their legal effects. The study further concludes that this theory has multiple applications, particularly in the areas of personal status law and the Jordanian Civil Code. Keywords: abuse of rights; exercise of rights; subjective criterion; Jordanian Civil Code.